Intellectually gifted students with possible characteristics of ASD: a multiple case study of psycho-educational assessment practices. Issue 1 (2nd January 2016) - Burger-Veltmeijer, Agnes E. J.; Minnaert, Alexander E. M. G.; Van den Bosch, Els J.
Abstract: The Strengths and Weaknesses Heuristic (S&W Heuristic) was constructed in order to reduce biased assessments of students with (suspicion of) Intellectual Giftedness in co-occurrence with Autism Spectrum Disorder (IG + ASD) and to establish a well-founded interconnection between assessment data and intervention indications. The current study is the second in the validation process of the S&W Heuristic. An in-depth analysis of three assessment dossiers of Dutch IG-students with possible characteristics of ASD is focused upon. The core question is whether the S&W Heuristic is of added value to diminish bias in any direction and increase systematicity. The results indicate that bias, mainly directed at Strengths, as well as unsystematicity were present in different stages of two assessment dossiers. The conclusion is that the S&W Heuristic seems to pave the way for systematicity and less bias in assessment processes of students with (suspicion of) IG + ASD.